Pengaruh Kualitas Pelayanan, Partisipasi Anggota dan Motivasi Berkoperasi Terhadap Sisa Hasil Usaha : (Studi Kasus pada Koperasi KSP Kopdit Pintu Air Cabang Lekebai) - Lorensius Jufrianus Siso; Pipiet Niken; Wihelmina Maryetha Yulia (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
This research aimed to examine the impact of member participation, service quality, and cooperative motivation on the business performance of KSP Kopdit Pintu Air Lekebai Branch. The research gathered primary data through the distribution of questionnaires to 97 members of the KSP Kopdit Pintu Air of Lekebai Branch. The data was analyzed using multiple linear regression analysis. Hypothesis testing was conducted using the F-test and t-test. Based on the descriptive analysis, the service quality variable falls into the "Fairly Good" category at 67.15%, member participation was at 62.04% in the same category, cooperative motivation was at 72.9% in the "Good" category, and the remaining business results variable was at 67.8% in the "Fairly Good" category. The t-test results indicate that service quality, member participation, and motivation to cooperate influence the remaining business results. Additionally, the F-test results show that service quality, member participation, and motivation to cooperate have a significant impact on the remaining business results. In conclusion, it can be inferred that service quality, member participation, and motivation to cooperate have a significant effect, either individually or collectively, on the remaining business results.